Bencana Badai Siklon Tropis Di Indonesia - Aisha Ramadhinia Annada; Rosalina Kumalawati (Universitas PGRI Palembang, 2023)
Tropical cyclones are powerful storms. Usually the average radius is around 150-200km. This tropical cyclone is formed above the sea where the sea water temperature is warm, more than 26.5 degrees Celsius, and strong winds whose rotation has a speed of 63km/hour. BMKG said that in Indonesia there were at least 12 tropical cyclones that occurred in the archipelago from 2008-2021. This research method uses descriptive methods via the internet, then analyzed using qualitative methods. The impact of tropical cyclones is extreme weather changes in Indonesia whose impacts we can see and feel are significant. BMKG also states that tropical cyclones are dangerous storms because they have enormous strength. The life span of tropical cyclones usually ranges from 3-18 days Because tropical cyclones get energy from warm oceans, tropical cyclones weaken when they move into areas of water where the temperature is cold. Another name for tropical cyclones is